Class II Phosphoinositide 3-Kinases as Potential Novel Drug Targets - Arcaro, Alexandre; Borgstrom, Anna; Blajecka, Karolina (Current Signal Transduction Therapy, 2013)
Phosphoinositide 3-kinases (PI3Ks) play an essential role in the intracellular signal transduction cascades initiated by the activation of cell surface receptors through their specific extracellular signals. PI3Ks control a variety of cellular responses, including growth, protection from apoptosis, motility, metabolism and intracellular protein sorting. Eight catalytic PI3K isoforms exist in human, which are grouped into three classes (I-III), based on structural homology and in vitro substrate specificity. Class I PI3Ks mediate signalling by receptor tyrosine kinases (RTKs) and G-proteincoupled receptors (GPCRs). The class II of PI3Ks, which comprises three distinct isoforms (PI3KC2α, PI3KC2β and PI3KC2γ) are less well characterized in terms of cellular functions. PI3KC2α and PI3KC2β are activated downstream of RTKs and GPCRs and play a role in cell migration, survival, glucose transport and endocytosis. Recently, the first isoform-specific small molecule inhibitors of PI3KC2β were described and evaluated as anti-proliferative agents in cancer. In this review, we will discuss the different regulatory mechanisms and functions of class II PI3Ks in the context of cell surface receptor signalling and their potential as novel drug targets in the field of oncology.
Keywords: receptor tyrosine kinase